Evaluating the impact of financial worry on mental health: a cross-sectional study among Kenyan radiographers - James Gitonga Ndung’u; Éva Bíró (BMC Public Health, 2024)
Abstract Background Psychological distress is a major public health concern that has many influencing factors. One of them is the financial capability of an individual. Despite the integral role of radiographers in healthcare delivery, there is limited literature about radiographers in Kenya and more so regarding their mental well-being. A descriptive cross-sectional study was conducted to evaluate the effect of perceived financial worry on mental health among Kenyan radiographers. Methods Data was collected from registered radiographers in Kenya through an online survey conducted between December 2023 and January 2024. Multivariable binary logistic regression was used to evaluate the association between financial worry and psychological distress. Results Out of the 2055 radiographers invited to participate in the survey, 245 responded (11.92% response rate). The gender distribution of the respondents was 39.2% female and 60.8% male, closely mirroring the latest data on registered radiographers (37.3% female and 62.7% male). Most respondents in our study were under 30 years old (56.7%). The majority of radiographers (62.4%) reported poor social support. Additionally, most radiographers experienced some level of financial concern across various issues, with an average financial worry score of 16.75 (standard deviation: 4.97; minimum 3, maximum 24). A significant proportion (36.7%) also showed signs of psychological distress. Individuals with higher levels of financial worry were noted to be more likely to experience psychological distress after adjusting for the socioeconomic and health-related variables (adjusted odds ratio, AOR 1.20, 95% confidence interval, CI 1.10–1.31, p < 0.001). Furthermore, individuals with at least moderate social support (AOR: 0.39; 95% CI 0.18–0.86, p = 0.019) and larger families (AOR: 0.11; 95% CI 0.02–0.78, p = 0.027) were less likely to experience psychological distress compared to their peers. Conclusions A significant number of radiographers reported experiencing financial worry which was associated with an increased likelihood of psychological distress. This emphasizes the need for policies and mechanisms to address financial worry and psychological distress to have a more resilient medical workforce in Kenya.